The Integration of Multiple Nuclear-Encoded Transgenes in the Green Alga Chlamydomonas reinhardtii Results in Higher Transcription Levels - Shahar, Noam; Landman, Shira; Weiner, Iddo; Elman, Tamar; Dafni, Eyal; Feldman, Yael; Tuller, Tamir; Yacoby, Iftach (Frontiers in Plant Science, 2020)
The integration of genes into the nuclear genome of Chlamydomonas reinhardtii is mediated by Non-Homologous-End-Joining, thus resulting in unpredicted insertion locations. This phenomenon defines ‘the position-effect’, which is used to explain the variation of expression levels between different clones transformed with the same DNA fragment. Likewise, nuclear transgenes often undergo epigenetic silencing that reduces their expression; hence, nuclear transformations require high-throughput screening methods to isolate clones that express the foreign gene at a desirable level. Here, we show that the number of integration sites of heterologous genes results in higher mRNA levels. By transforming both a synthetic ferredoxin-hydrogenase fusion enzyme and a Gaussia-Luciferase reporter protein, we were able to obtain 33 positive clones that exhibit a wide range of synthetic expression. We then performed a droplet-digital polymerase-chain-reaction for these lines to measure their transgene DNA copy-number and mRNA levels. Surprisingly, most clones contain two integration sites of the synthetic gene (45.5%), whilst 33.3% contain one, 18.1% include three and 3.1% encompass four. Remarkably, we observed a positive correlation between the raw DNA copy-number values to the mRNA levels, suggesting a general effect of which transcription of transgenes is partially modulated by their number of copies in the genome. However, our data indicate that only clones harboring at least three copies of the target amplicon show a significant increment in mRNA levels of the reporter transgene. Lastly, we measured protein activity for each of the reporter genes to elucidate the effect of copy-number variation on heterologous expression.